2016
DOI: 10.1111/1744-9987.12468
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin Balance in Septic Shock Patients With Acute Kidney Injury: Effects of Direct Hemoperfusion With Polymyxin B‐Immobilized Fiber

Abstract: Acute kidney injury (AKI) occurs in approximately 50% of patients in septic shock, and mortality from septic AKI is extremely high. Angiopoietin levels may play a role in the pathogenesis of vascular permeability. It was reported that direct hemoperfusion with a polymyxin B-immobilized fiber column (DHP-PMX) therapy ameliorates the angiopoietin balance in patients with sepsis. Although dysregulated angiopoietin balance in sepsis has been demonstrated, mechanisms underlying the development of AKI in sepsis have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Further, an activated thromboxane A2 pathway causes platelet adhesion, capillary thrombosis and mediates vasoconstriction, decreasing kidney blood flow and function 38 – 40 . These findings are in line with other studies reporting the role of endothelial dysfunction in the development of sepsis-AKI 41 , 42 , 43 . Together, plasma proteomic profile of sepsis patients strongly suggest that endothelium dysfunction precedes development of acute kidney injury, suggesting that an endothelium protective strategy early in sepsis may protect from the development of sepsis-AKI.…”
Section: Discussionsupporting
confidence: 93%
“…Further, an activated thromboxane A2 pathway causes platelet adhesion, capillary thrombosis and mediates vasoconstriction, decreasing kidney blood flow and function 38 – 40 . These findings are in line with other studies reporting the role of endothelial dysfunction in the development of sepsis-AKI 41 , 42 , 43 . Together, plasma proteomic profile of sepsis patients strongly suggest that endothelium dysfunction precedes development of acute kidney injury, suggesting that an endothelium protective strategy early in sepsis may protect from the development of sepsis-AKI.…”
Section: Discussionsupporting
confidence: 93%
“…92 Table 1 summarizes some biomarkers studied in S-AKI. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] Neutrophil gelatinase-associated lipocalin (NGAL) has been extensively investigated in various AKI phenotypes. NGAL is released by activated neutrophils and various epithelial cells including renal TECs.…”
Section: Role Of Biomarkers In S-akimentioning
confidence: 99%
“…In addition, one of the most common complications of septic shock is acute kidney injury (AKI) and it occurs in more than 20% of patients with sepsis that is related to higher mortality rate[28]. Ebihara et al[29] suggested that PMX-HP restored the angiopoietin-1 levels and diminished the levels of angiopoietin-2 in septic AKI, thereby preventing the apoptosis of renal tubular cells resulting in a protective effect against AKI[19]. Our results demonstrated a dramatic decrease in renal SOFA score, and considering the high mortality of septic AKI, authors expect that the removal of endotoxin or cytokines might protect the renal function in abdominal septic shock.…”
Section: Discussionmentioning
confidence: 99%